Knowledge, Attitude and Practice of Family Planning among Women of Reproductive Age (Journal of Dhaka National Medical College & Hospital, 2017)
Background: Family planning is regarded as an important preventive measure against maternal and child morbidity and mortality. This study was aimed at determining the knowledge, attitude and use of family planning methods among women of reproductive age (15-49 yrs.) attending indoor and outdoor department of Dhaka National Medical College & Hospital.Objective: The aim of this study was to explore the awareness and practice of family planning among women of reproductive age.Material and methods: This descriptive cross sectional study was conducted among the women of reproductive age attending indoor and outdoor department of Dhaka National Medical College. Data was collected by face to face interview with pre-tested questionnaire.Place and period of study: The study was conducted during September 2012 to October2013 in Dhaka National Medical College.Result: 200 female of reproductive age were studied. The mean age was 27.52±5.2. Of the total subjects 194 (97%) were aware of contraception. 182 (91%) used contraceptive methods and 18 (9%) did not. Religious prohibition, in-laws disapproval, husband disapproval, need more child and lack of awareness act as a barrier in using contraceptive methods. Of the contraceptive user 171 (93.9%) used temporary methods and 11 (6%) used permanent methods. Those who used temporary methods, majority 99 (58%) used hormonal preparation followed by 50 (29.2%) used barrier methods, 16 (9.3%) used natural method and 6 (3.5%) used IUDs. of the permanent method user 9 (81.8%) had tubectomy and 2 (18.2%) husband had vasectomy.Conclusion: This study concludes that there is a gap among knowledge, attitude and practice in the use of family planning methods. Though most of them use contraceptive methods but some social factors affect the practice. So effective couple counseling should be done.J, Dhaka National Med. Coll. Hos. 2017; 23 (01): 08-11